Futuros pasados, futuros perdidos. Reconfiguraciones de la memoria de los setenta en la Argentina de los noventa - Mora González Canosa (Centre de Recherches sur les Mondes Américains, 2011)
The article analyzes some memory reconfigurations about the political radicalization process prior to Argentina’s last military dictatorship (1976-1983) that took place in the mid-nineties. By then the social elaboration of the repressive experience began to transit from a depoliticizing discourse that had conceived people who suffered state terror as "innocent victims" to another that sought to vindicate the political action and militancy of the disappeared. The aim is to approach this issue by analyzing one of the "vehicle of memory" paradigmatic of this process of passage, the documentary Hunters of Utopias, and the debate provoked by the movie premiere in the newspaper Página/12. The paper examines the memory strategies deployed by the film, specifying its place of enunciation and the way that from there gives meaning to the narrated past, in the light of its socio-political conditions of production and those memories with which confronts. In the same direction analyzes the controversy appeared in Pagina/12, that transcended the consideration of the film to focus on what should be the senses, legacies and ways of transmission of the seventies experience, involving different generations that put into play wich should be the role that each of them in the process of reappropriation of that militant past.